Manufacturing technology of Garuda Mulia concrete roof tiles/wave roof tiles and Mulia flat roof tiles using Padang cement at the port of Gresik - Budiono, Agus (Edelweiss Applied Science and Technology, 2025)
Wave roof tiles and flat roof tiles are effective roofing materials. The Malang area possesses significant iron sand potential, especially from Mount Arjuno. Iron sand has high tensile strength, making it suitable as a mixture component for manufacturing wave and flat roof tiles. This research employs experimental methods to investigate the effects of Padang Cement on the production of these tiles, with specific compositions including 40% sand, 15% stone ash, 30% cement, 15% fly ash, and supporting materials for wave roof tiles. Additionally, the study compares wave roof tiles made using a mixture of Malang sand. Comparative testing of concrete roof tiles with Padang Cement involved flexural load tests and water seepage resistance tests on wave roof tiles, as well as water absorption tests on both wave and flat roof tiles. The results indicated an average bending load of 2122.68 N. Water resistance tests showed that water did not penetrate the tiles, and no droplets were observed at the bottom of the concrete or flat roof tiles. Regarding water absorption, the average wave tile exhibited an absorption rate of 3.8%, while the flat tile had an absorption rate of 3.3%. Based on these findings, it can be concluded that both flat and wave concrete roof tiles meet the standards specified in SNI 0096-2007 and PUBI-1982, demonstrating their suitability as durable roofing materials.